2000
DOI: 10.1093/humrep/15.5.1189
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcome of pregnancies following ICSI, classified according to sperm origin and quality

Abstract: The aim of this study was to report the outcome of all clinical pregnancies obtained after intracytoplasmic sperm injection (ICSI) performed during a 5 year period at two fertility clinics, with special reference to delivery outcome associated with different sperm origin and quality and the transfer of fresh or frozen-thawed pre-embryos. A total of 1293 clinical pregnancies was analysed. Deliveries occurred in 75.9% (n = 982) and early spontaneous abortion, late spontaneous abortion and ectopic pregnancy in 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 30 publications
3
30
1
Order By: Relevance
“…A 2010 systematic review of five studies comparing the source of the sperm demonstrated no significant differences between the groupings in terms of risk for congenital malformations. 39 The range of frequencies of congenital malformations in ejaculated sperm was from 1.9% 40 to 8.4%, 41 for epididymal sperm from 2.0% 40 to 4.3% 42 and for testicular sperm from 0% 42 to 9.2%. 41 Within each study, there were no significant differences in risk of congenital malformations, although the range of frequencies reflects the inconsistencies mentioned earlier in regard to ascertainment of congenital malformations.…”
Section: Overall Defectsmentioning
confidence: 97%
“…A 2010 systematic review of five studies comparing the source of the sperm demonstrated no significant differences between the groupings in terms of risk for congenital malformations. 39 The range of frequencies of congenital malformations in ejaculated sperm was from 1.9% 40 to 8.4%, 41 for epididymal sperm from 2.0% 40 to 4.3% 42 and for testicular sperm from 0% 42 to 9.2%. 41 Within each study, there were no significant differences in risk of congenital malformations, although the range of frequencies reflects the inconsistencies mentioned earlier in regard to ascertainment of congenital malformations.…”
Section: Overall Defectsmentioning
confidence: 97%
“…87 Neither obstetric outcome of ICSI pregnancies nor child development of ICSI offspring was different from conventional IVF and not influenced by sperm origin or quality. 88,89 When epididymal sperm is used for ICSI, stillbirths or congenital malformations are not more prevalent in comparison to IVF and ICSI using ejaculated sperm, while cognitive development was also similar. 90,91 While aneuploidy screening on embryos obtained after ICSI for NOA showed increased aneuploidy and mosaicism, 92 and karyotypes of miscarriages occurring after TESE-ICSI showed higher aneuploidy rates than expected, 93 the few publications focusing on the outcome of children born after ICSI using testicular sperm conclude that no significant differences exist between ICSI using ejaculated spermatozoa or ICSI using testicular spermatozoa in terms of birth weight, perinatal mortality and major malformation rate.…”
Section: Outcomes After Icsimentioning
confidence: 99%
“…After ICSI, ejaculated or surgically extracted sperm, when motile and morphologically normal, result in similar fertilization, implantation [108,109] and clinical pregnancy rates ( [109]. The incidence of early or late spontaneous abortion and ectopic pregnancy, or malformations is also similar [108].…”
Section: Sperm Originmentioning
confidence: 99%
“…After ICSI, ejaculated or surgically extracted sperm, when motile and morphologically normal, result in similar fertilization, implantation [108,109] and clinical pregnancy rates ( [109]. The incidence of early or late spontaneous abortion and ectopic pregnancy, or malformations is also similar [108]. However, after conventional IVF, even testicular or epididymal aspirates with very good sperm concentration and motility, generally achieve low fertilization and pregnancy rates [110].…”
Section: Sperm Originmentioning
confidence: 99%